Understanding community variation and vhange in Ethiopia: Implications for children - Pankhurst, A; Tiumelissan, A (Young Lives, 2012)
Changes that happen within communities can have considerable consequences for the lives of children and their families. This paper demonstrates the importance of considering the community context and shows how differences between sites can be significant. The authors consider changes in the lives of children and young people in 20 sites in Ethiopia (eight urban and twelve rural) that were the subject of three rounds of field work by Young Lives researchers between 2002 and 2009. They assess the impact on family life of changes in the local economies and livelihoods (including types of production, the frequency of shocks, food insecurity, and the extent of dependence on food assistance); the social and economic impacts of improved access to transport, telecommunications and electricity; and the interaction between prevailing cultural values and external interventions that seek to bring about change, particularly in relation to gender issues and child protection. They describe changes in the context of child-protection services, with an increasing role for government, particularly the Ministry of Women, Children and Youth Affairs, in collaboration with NGOS and informal community-initiated institutions. They note that there has been a broadening of interest from the needs of HIV/AIDS orphans to those of vulnerable children more generally, and to interventions against customs viewed as Harmful Traditional Practices, notably early marriage, especially in Tigray. It is suggested that appreciating the implications of changes at community level for households and children could help to explain changes in children’s lives over the rounds of study, and it is hoped that the approach adopted in this paper will stimulate further work to improve understanding of the nature of childhood poverty.